2014
DOI: 10.3233/ves-130506
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous promethazine versus lorazepam for the treatment of peripheral vertigo in the emergency department: A double blind, randomized clinical trial of efficacy and safety

Abstract: Background: Vertigo imposes considerable health restrictions with significant impact on the patient's quality of life. The most effective antivertigo agent is undetermined thus far. Objective: This study was performed to assess whether promethazine has superior vertigo reduction compared with lorazepam in ED patients. Methods: In this randomized, double-blind, parallel group trial 184 patients were assigned (1:1 ratio) to receive either promethazine, 25 mg intravenously, or lorazepam, 2 mg intravenously. Prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…The effect of intravenous promethazine (25 mg) and intravenous lorazepam (2 mg) was checked on 184 visitors of the emergency section of Imam Hossein University affiliated with Shahid Beheshti University. This research showed that the former medicine was more effective in treating acute peripheral vertigo than the latter [21]. The overall findings revealed that promethazine was more effective in treating acute peripheral vertigo than benzodiazepines.…”
Section: Consort Flow-chartmentioning
confidence: 76%
See 2 more Smart Citations
“…The effect of intravenous promethazine (25 mg) and intravenous lorazepam (2 mg) was checked on 184 visitors of the emergency section of Imam Hossein University affiliated with Shahid Beheshti University. This research showed that the former medicine was more effective in treating acute peripheral vertigo than the latter [21]. The overall findings revealed that promethazine was more effective in treating acute peripheral vertigo than benzodiazepines.…”
Section: Consort Flow-chartmentioning
confidence: 76%
“…Group A received a treatment with intravenous promethazine (10 mg) made by Caspian Company. The checklist consisted of demographic information, history of disease, severity of vertigo upon admission to emergency section, symptoms upon admission, patient's full examinations, response to treatment, reduction of the severity of symptoms, side effects of treatment and treatment courses [21]. It is noteworthy that 50 mg of promethazine and 10 mg of diazepam are each equal to 1 cc, as used in this study [22].…”
Section: Population and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…53 There are few high-grade clinical trials of pharmacologic treatments of vertigo in acute presentations. [54][55][56][57][58] Available studies focus on heterogenous vertigo populations or acute peripheral vertigo presentations without other criteria to make it more specific to certain entitles. The studies are also limited by their outcome measures, which were typically 10-point severity scales obtained 30 minutes to 2 hours after treatment.…”
Section: Treatment Of the Acute Vestibular Syndromementioning
confidence: 99%
“…Бензодиазепины длительного действия, например феназепам, при ВГ не эффективны [4]. Недавно проведенное сравнительное исследование эффективности лоразепама и прометазина продемонстрировало большую эффективность последнего в качестве препарата для купирования ВГ [5].…”
unclassified